2023
DOI: 10.3390/rs15143600
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Five Machine Learning Algorithms for Supervised Object-Based Classification of Submerged Seagrass Beds Using High-Resolution UAS Imagery

Abstract: Knowledge about the spatial distribution of seagrasses is essential for coastal conservation efforts. Imagery obtained from unoccupied aerial systems (UAS) has the potential to provide such knowledge. Classifier choice and hyperparameter settings are, however, often based on time-consuming trial-and-error procedures. The presented study has therefore investigated the performance of five machine learning algorithms, i.e., Bayes, Decision Trees (DT), Random Trees (RT), k-Nearest Neighbor (kNN), and Support Vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…The depth measurements collected by the payload system (Figure 8) could be interpolated to a detailed bathymetry map of the study area using the spline interpolation method (Figure 11a). Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42]. Nevertheless, detailed bathymetry maps are often not Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42].…”
Section: Interpolation Of Depth Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth measurements collected by the payload system (Figure 8) could be interpolated to a detailed bathymetry map of the study area using the spline interpolation method (Figure 11a). Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42]. Nevertheless, detailed bathymetry maps are often not Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42].…”
Section: Interpolation Of Depth Measurementsmentioning
confidence: 99%
“…Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42]. Nevertheless, detailed bathymetry maps are often not Shallow-water bathymetry is an important factor that greatly influences environmental processes in the coastal zone and is therefore a crucial input parameter for many benthic habitat assessments [47] and ecological models [41], which in turn are used by coastal managers for policy making [42]. Nevertheless, detailed bathymetry maps are often not available due to the ineffectiveness and limitation of traditional techniques, such as boat surveys, in shallow waters.…”
Section: Interpolation Of Depth Measurementsmentioning
confidence: 99%
“…This relationship between the size of algal beds and their CO 2 absorption ability shows the importance of accurate area measurements in evaluating their role in blue carbon strategies [9]. Several studies have demonstrated the feasibility of identifying algal beds by analyzing aerial or unmanned aerial vehicle images, even though their primary focus has been on the detection of seaweed presence rather than blue carbon assessment [10,11].…”
Section: Introductionmentioning
confidence: 99%